Balinese Classical Prasi: Visual Beauty and Meaning Behind the Lontar Engravings - I Nyoman Sila; Ummi Risti Ayuni Rahman; Ni Komang Widiani; Jian Bang Deng (Universitas Negeri Semarang, 2026)
Prasi, as a traditional artwork, has unique characteristics by displaying the identity of Balinese art and culture. It is a manuscript on palm leaves with wayang illustrations, sometimes accompanied by short text in Balinese characters. Prasi has aesthetic and classical value because the materials and equipment used, production techniques, and wayang form are still traditional. As an artwork, Prasi conveys a symbolic meaning through the story it depicts. This paper describes: (1) a critical review of the aesthetic value and natural character of the raw materials of Prasi; (2) a critical review of the visual aspects of the image and its configuration on palm leaf blades to produce Prasi artwork of good artistic value. Data were collected by purposive sampling by looking for prominent artists and community leaders who know about Prasi. Collecting data is done through observation, interviews, and documentation. The data obtained are grouped based on the type of data, then analyzed using qualitative descriptive methods. The results showed: (1) the aesthetic value of Prasi raw materials from palm leaves is processed to produce a smooth and durable surface, so it is easy to cut using pengrupak to display wayang images assembled from several palm leaves; (2) the visual aspect of Prasi art is artistically composed of elements of line, plane, color, texture, and space through the form of classical wayang images and other supporting decorative motifs in a series of stories taken from the Ramayana, Mahabharata, and traditional Balinese stories that have aesthetic value.